Relationship between inherited genetic variation and survival from colorectal cancer stratified by tumour location - Wills, C; Watts, K; Houseman, A; Maughan, TS; Fisher, D; Al-Tassan, NA; Houlston, RS; Escott-Price, V; Cheadle, JP (Nature Research, 2025)
The location of a patient’s colorectal cancer (CRC) influences their outcome but inherited factors may also be involved. We studied 1899 patients with advanced CRC (514 had proximal colonic, 493 distal colonic and 892 rectal tumours) and carried out genome-wide association studies for survival. Single nucleotide polymorphisms (SNPs) suggestive of association (P < 1.0 × 10–5) were tested for replication in 5078 CRC patients from the UK Biobank. We investigated the relationship between Phosphatidylinositol 4-Kinase Type 2 Beta (PI4K2B) expression in colorectal tumours and survival in 597 patients from The Human Protein Atlas (THPA). We also analysed 3 SNPs previously associated with survival by anatomical site. We found that SNPs at 54 independent loci were suggestive of an association with survival when stratified by tumour location. rs76011559 replicated in patients with proximal tumours (COIN, COIN-B and UK Biobank combined Hazard Ratio [HR] = 1.53, 95% Confidence Intervals [CI] = 1.19–1.86, P = 7.5 × 10–7) and rs12273047 replicated in patients with rectal tumours (combined HR = 1.27, 95% CI = 1.09–1.46, P = 4.1 × 10–7). In gene analyses, PI4K2B associated with survival in patients with distal cancers (P = 2.1 × 10–6) and increased PI4K2B expression in colorectal tumours was associated with improved survival (P = 9.6 × 10–5). No previously associated SNPs were replicated. Our data identify novel loci associated with survival when stratified by tumour location.